Addressing inadequate complementary feeding practices in Pakistan: a call to action - Syeda Zil-e-Zehra Naqvi; Manan, Hamna (Journal of the Pakistan Medical Association, 2025)
I am writing to highlight the matter of utmost importance regarding inadequate complementary feeding practices in Pakistan, especially for children under 5 years old. It has been widely known that child nutrition during formative years plays a crucial role in their long-term growth and development. WHO recommends exclusive breastfeeding for the first 6 months of life [1]; however, after that, a child’s nutritional needs surpass what breast milk alone can provide, making initiating complementary feeds imperative for optimal growth and development. Fortunately, due to massive efforts from all stakeholders, where breastfeeding practices have increased in Pakistan [2], the country still faces significant challenges in ensuring adequate complementary feedings for children. According to the most recent Nutritional Survey, where on one hand, 4 out of 10 children suffer from stunting, and 30 % of children under 5 are underweight, Simultaneously, the prevalence of obesity in this age group has risen from 5% in 2011 to 9.5% in 2018. Regardless of their weight status, children under five face a significant burden of micronutrient deficiencies, including iron, vitamin D, and vitamin A. Significant probing is required through extensive research and studies to have a clearer picture of the dilemma of inadequate nutrition among children. However, in an overview of the situation, it can be concluded that children in our country lack a healthy diet that provides them with all micro and macro nutrients along with maintaining a healthy weight. Healthcare workers should be aware of this situation, keep these prevalence’s in mind, and regularly check and treat children during routine visits for these micro and macronutrient deficiencies to prevent their long-term detrimental consequences. Physicians should take detailed, tailored nutritional and socioeconomic histories to find the exact culprits and address them accordingly. The increasing prevalence of obesity should not be overlooked as it can be hazardous for our country, which is already facing a huge burden of diabetes [3]. Parents should be warned about choosing processed foods, especially those containing additive sugar, for their children, as they can significantly contribute to the rising trends of obesity [4]. In conclusion, the present condition of complementary feedings calls for extensive research and practical steps by all stakeholders to ensure that every child in Pakistan receives safe, healthy, and nutritionally efficient food that helps them reach their full growth potential.